2017
DOI: 10.15171/ehem.2017.07
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of chemical characteristics and spatiotemporal quantitative changes of dust fall using GIS and RS technologies; a case study, Yazd city, central plateau of Iran

Abstract: Background: The phenomenon of dust is a serious environmental problem in dry and semi dry regions. It has a destructive effect for the residents of such regions. Over two-thirds of Iran is in areas of dry and semi-dry climate conditions. Methods: In this research, dust fall measurements were taken in 41 stations across Yazd city using a marble dust collector (MDCO) located in different parts of the city. Next, the chemical characteristics of dust were determined using the XRF method. Finally, levels of dust fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Numerous articles have been satisfied with the information provided by meteorological stations. Another category of studies was to study and to provide the zoning map of spatial distribution of dust in the study area (Azimzadeh et al, 2010) and another group of studies tried to interpolate and distinguish the concentration of heavy elements found in dust particles (Ismail-Zadeh-Hosseini et al, 2013). The resulting map is a qualitative division for various regions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous articles have been satisfied with the information provided by meteorological stations. Another category of studies was to study and to provide the zoning map of spatial distribution of dust in the study area (Azimzadeh et al, 2010) and another group of studies tried to interpolate and distinguish the concentration of heavy elements found in dust particles (Ismail-Zadeh-Hosseini et al, 2013). The resulting map is a qualitative division for various regions.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific research conducted in the last two decades has shown that particles are one of the critical pollutants from the point of view of health effects (such as eye irritation, dry throat, runny nose, sneezing, coughing, tiredness, irritability, difficulty concentrating, headaches, cardiovascular effects, hypertension, obesity, and type 2 diabetes mellitus), cancer health risks, and mortality ( 8 ). The WHO estimated the annual cost of air pollution in Austria, France, and Switzerland to be about 30 billion pounds and that air pollution-related deaths accounted for 6% of all deaths in those countries ( 9 ). Particulate matter (PM) with an aerodynamic diameter of ≤2.5 μm (PM 2.5 ) significantly affects health and increases mortality rates due to respiratory, cardiovascular, and lung diseases ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Relative to SO2 and NO2, PM10 concentration in Hyderabad, India was extremely higher than the WHO prescribed values to more than 3 order consistently in years (2016-2018) 3 . PM pollution can become a serious environmental problem especially when regions suffer from a dry climatic condition 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Mapping of air pollution is one approach of monitoring air pollution and prediction of monitored pollution level provided reliable estimates 10 . Mapping of air quality (AQ) through GIS was utilized to evaluate the cost of health care of exposed individuals to various air pollutants estimating economic costs due to health damage 11 , characterizing elemental constituents of dust 4 and understanding land cover and human activities impacts to air pollutant emission 9 . The IDW technique was utilized in various air pollution studies 3,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%